Reaching the top of Bloom’s Taxonomy: an innovative pilot program for preclinical undergraduate and medical school students to create curricula for STEMM outreach/service-learning programs - Abigail Salas; Mingqian Tan; Sofia Andrienko; Kayra Cengiz; Jonathan J. Wisco (Frontiers in Education)
Bloom’s Taxonomy is an andragogical tool that classifies educational objectives, learning activities, and assessments into distinct levels of cognitive thinking. Preclinical medical sciences educators aim to promote higher-order thinking in their curricula to help students develop clinical decision-making skills and foster deep learning. However, many courses and curricula remain focused on lower levels of Bloom’s Taxonomy because they are easier to implement and assess. Meanwhile, many service-learning opportunities for medical students focus on developing affective faculties over higher-level cognitive processing of curricular material. We describe a model program in which undergraduate pre-medical education (UPE) and undergraduate medical education (UPE/UME) students at Boston University Charles River Campus (BU CRC) and Boston University Aram V. Chobanian & Edward Avedisian School of Medicine (BU Chobanian & Avedisian SOM) simultaneously engaged in service-learning and the Create level of Bloom’s Taxonomy by developing a supplementary high school (HS) medical science curriculum based on content and instructional models from their preclinical courses. Activities such as mock patient cases, simulated patient interviews, and physical examination training contributed toward a HS curriculum that promotes healthy habits; increases community public health self-efficacy; sparks interest in Science, Technology, Engineering, Math and Medicine (STEMM) concepts; and educates about medical careers through engaging lessons and activities focused on human anatomy and physiology.